Typical Venice?: The art of commodities 13th-16th centuries - Beaucamp, Ella; Cordez, Philippe (Harvey Miller Publishers, 2020)
This book focuses on the question of how Venice designed and exported its own identity through all kinds of its goods. What are "Venetian" commodities? More than any other medieval or early modern city, Venice lived off of the trade of portable goods. In addition to trading foreign imports, the city also engaged in intense local production, manufacturing high quality glass, crystal, cloth, metal, enamel, leather, and ceramic objects, characterized by their exceedingly rich forms and complex production processes. Today, these objects are scattered in collections throughout the world, but little remains in Venice itself. In individual instances, it is often difficult to tell whether the objects in question were actually made in Venice or if they originated in Byzantine, Islamic, or other European contexts. This book focuses on the question of how Venice designed and exported its own identity through all kinds of its goods
Keywords: Aufsatzsammlung; Geschichte 1200-1600; Handel; Kunsthandwerk; Venedig